Effects of White Potatoes Consumed With Eggs on Satiety, Food Intake, and Glycemic Response in Children and Adolescents. (17th February 2020) - Lee, Jennifer J.; Brett, Neil R.; Chang, Jennifer T.; de Zepetnek, Julia O. Totosy; Bellissimo, Nick
Abstract: Objective: Short-term studies in adults have shown that white potatoes increase satiety and suppress food intake (FI) compared with several other carbohydrate-containing foods; however, studies are limited in children. The objective was to compare the effects of white potatoes in mixed meals on satiety, FI, and glycemic response in 9-14-year-old children and adolescents. Methods: Using a within-subject, repeated-measures design, 21 children completed five counter-balanced test sessions. After an overnight fast, children consumed one of four isocaloric treatment meals (450 kcal) of French fries, mashed potatoes, or white beans served with a fixed portion of egg omelet (30 g of protein), a control meal with cereal, milk, and bread, or continued to fast (i.e., meal skipping). Subjective appetite was measured using visual analogue scales. FI at an ad libitum pizza meal at 180 min and rest of day diet record were used to measure lunch FI and rest of day energy intake, respectively. Total daily energy intake was calculated by adding the energy intake from the treatment meal, the ad libitum pizza lunch, and rest of day food record. Capillary blood samples were collected to assess glycemic response over 180 min. Results: Change from baseline subjective average appetite scores were lower after mashed potatoes compared with all other treatment conditions (p < 0.001), and higher after French fries compared with white beans (p = 0.04). Lunch FI (kcal) was significantly lower (p < 0.001) after French fries (1010±73) and mashed potatoes (1039±74) compared with the control meal (1257±92) and meal skipping (1235±74). Total daily energy intake (kcal) was lower after French fries compared with the control meal (2228±141 vs. 2624±137; p = 0.04). Change from baseline blood glucose was lower after white beans and French fries compared with mashed potatoes (p < 0.05) and the control meal (p < 0.001). Conclusion: In conclusion, white potatoes with eggs increased satiety, decreased short-term FI, and resulted in similar energy intakes compared with meal skipping.